Comparison of the Provisions of the Austrian and German Criminal Procedure Laws on Victims with the Hungarian Legislation - Somogyi, Csilla (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Victims are necessary participants in the criminal process, but until the 20th century they were marginalised. Since then legislators have recognised the importance of victim protection. The Council of Europe and the European Union are also striving to regulate victims' rights and to establish minimum standards, naturally with special emphasis on the rights and protection of the most vulnerable victims. The preamble of the Hungarian Criminal Procedure Act treats the increased protection of victims and the enforcement of their rights as a priority objective. In my study, I will compare the provisions of the Hungarian Criminal Procedure Act with the provisions of the Austrian and German laws on victims. I have chosen these two countries for the comparison because the Hungarian legal system, due to its historical traditions is the closest to them. I believe that it is primarily the practice of these two countries that should be examined and compared with Hungarian legislation.